2015
DOI: 10.1007/s11302-015-9475-2
|View full text |Cite
|
Sign up to set email alerts
|

Guanosine inhibits LPS-induced pro-inflammatory response and oxidative stress in hippocampal astrocytes through the heme oxygenase-1 pathway

Abstract: Guanosine, a guanine-based purine, is an extracellular signaling molecule that is released from astrocytes and has been shown to promote central nervous system defenses in several in vivo and in vitro injury models. Our group recently demonstrated that guanosine exhibits glioprotective effects in the C6 astroglial cell line by associating the heme oxygenase-1 (HO-1) signaling pathway with protection against azideinduced oxidative stress. Astrocyte overactivation contributes to the triggering of brain inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 70 publications
5
45
0
Order By: Relevance
“…Within this context, it has been shown that this nucleoside is able to prevent the production of reactive oxygen species (ROS) and to counteract alterations in inflammatory parameters, such as an increase in interleukin 6 (IL-6) and tumor necrosis factor alpha (TNF-α) and a decrease in the levels of the antiinflammatory cytokine interleukin 10 (IL-10) [92,93]. Furthermore, the guanosine-induced activation of the PI3K/Akt and MAPKs signaling pathways is also related to the inhibition of nuclear factor-kappaB (NF-κB) and inducible nitric oxide synthase (iNOS) [82,83,94] and with the induction of the expression of hemeoxygenase-1 (HO-1) [53,83,92,94].…”
Section: Metabolism and Intracellular Signaling Pathways Triggered Bymentioning
confidence: 99%
See 2 more Smart Citations
“…Within this context, it has been shown that this nucleoside is able to prevent the production of reactive oxygen species (ROS) and to counteract alterations in inflammatory parameters, such as an increase in interleukin 6 (IL-6) and tumor necrosis factor alpha (TNF-α) and a decrease in the levels of the antiinflammatory cytokine interleukin 10 (IL-10) [92,93]. Furthermore, the guanosine-induced activation of the PI3K/Akt and MAPKs signaling pathways is also related to the inhibition of nuclear factor-kappaB (NF-κB) and inducible nitric oxide synthase (iNOS) [82,83,94] and with the induction of the expression of hemeoxygenase-1 (HO-1) [53,83,92,94].…”
Section: Metabolism and Intracellular Signaling Pathways Triggered Bymentioning
confidence: 99%
“…1), it is not surprising that this nucleoside was shown to be neuroprotective both in vitro and in vivo against a plethora of different insults, including excitotoxins [95,96], apoptosis induced by staurosporine [86], stress-induced oxidative damage [97], sepsis-induced cognitive impairment [98], hepatic encephalopathy [99], azide-induced oxidative damage [100], lipopolysaccharide (LPS)-induced inflammation [94], ischemic damage [63,101,102], toxicity induced by amyloid β peptide (Aβ) [91,103] as well as 1-methyl-4-phenylpyridinium (MPP + ) and 6-hydroxydopamine (6-OHDA) [36,[104][105][106], and spinal cord injury (SCI) [107,108]. Based on these studies, the modulation of the purinergic system has emerged as a therapeutic approach for the treatment of various neurological conditions, and guanosine in particular may be a therapeutic target for several of these neuropathologies.…”
Section: The Effects Of Guanosine In Cns Neuropathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Guanosine, more specifically, has been shown to induce numerous beneficial cellular responses in several brain injuries, such as seizures, hypoxia, anxiety-like behavior, ischemia, and glucose deprivation [1,[6][7][8][9]. In addition to demonstrating the ability to modulate glutamatergic metabolism, avoiding the overactivation of glutamate receptors, and exerting antioxidant and anti-inflammatory activities [10][11][12], guanosine can also modulate several signaling pathways to provide neuroprotection [1,13,14]. However, despite the increasing evidence of the protective effects of guanosine in neural cells, its mechanism of action is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has previously demonstrated the interplay between guanosine and the enzyme heme oxygenase 1 (HO-1) [12,14], which is the major enzyme responsible for the conversion of heme into CO and the antioxidant products biliverdin and bilirubin [15,16]. It has been reported that HO-1 may be a therapeutic target in the aging process and/or neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%